Comparative study on nutritional status, food intake pattern and lifestyle between dialyzed and non-dialyzed kidney patients in Dhaka, Khulna and Rajshahi divisions of Bangladesh - Islam, Md Tanvir; Mukta, Nurun Nahar (Asian-Australasian Journal of Food Safety and Security, 2017)
Chronic kidney disease (CKD) is a worldwide public health problem. As per nephrologists' estimation, the CKD population grows at approximately 5% annually and in 2022, over 29 million people will be afflicted with CKD in Bangladesh. The objective of this study was to compare nutritional status, food intake pattern, and lifestyle between dialyzed and non-dialyzed kidney patients in Bangladesh. It was a cross-sectional comparative study of patients aged 18 to 85 year old to compare nutritional status, food intake pattern, and lifestyle between dialyzed and non-dialyzed kidney patients. Sample was conducted in three divisions Dhaka, Khulna and Rajshahi in Bangladesh. Data on food intake pattern, height, weight, GFR, other diseases along with kidney disease, physical activity, smoking and socioeconomic status etc. were collected from fifteen clinical centers and sometimes from household via in-person interviews. A total of 244 patients aged were selected among them 152 people were dialyzed patients and 92 people were Non-dialyzed patients. We found a relationship among dietary food habit, lifestyle factors and health outcomes such as chronic kidney disease progression, heart disease and death. Patients had a mean monthly family income of 23683.46, a mean monthly expenditure on food of 3815.2 and a mean monthly expenditure on treatment of 13317.69. According to our findings, highest dialysis patients were sedentary than non-dialysis patients were active at their active life (20-40 Years). From this study it was investigated that, 41.0% patients have not changed their addiction habit after diagnosis, where 20.1% dialysis patients and 20.9% non-dialysis patients have not changed their addiction habit totally. Another significant finding of this study was that dialysis patients had poor consumption from 16 groups. It can be highlighted that, the prevalence of the diseases were higher in urban people than rural people. This study suggests that additional research is needed to investigate the optimal dietary recommendations and body mass index levels to prevent disease progression and poor outcomes among individuals with CKD. The prevalence of HD-CKD and NDD-CKD can be said to be SES dependent. Chronic kidney disease and its complications, which involve most organ systems, can be prevented, but awareness and use of accurate methods are needed to enable timely diagnosis. Asian Australas. J. Food Saf. Secur. 2017, 1 (1), 25-34